First report of Nigrospora sp. causing kiwifruit postharvest black rot. Issue 1 (2nd January 2017) - Kwon, Youngho; Kim, Minjung; Kwack, Yong-Bum; Kwak, Youn-Sig
ABSTRACT: In February 2016 in Sacheon, South Korea, symptoms similar to 'black rot' symptoms caused by Nigrospora sp. were observed in kiwifruit stored between 0°C and 1°C. Symptoms included the presence of sunken lesions on the fruit pericarp, which were watery and black in the centre. The causal agent was identified as Nigrospora sp. by morphological characteristics and by sequencing the internal transcribed spacer region of rDNA. The Koch's postulate was confirmed by inoculating kiwifruit with the pathogen. After two weeks at 16°C, the pathogen was re-isolated from inoculated lesions and confirmed to have genetic characteristics similar to the strain used for inoculation. To our knowledge, this is the first report of kiwifruit postharvest black rot caused by Nigrospora sp. and this information will aid in control of postharvest disease in the kiwifruit industry.